2019
DOI: 10.1210/jc.2018-02772
|View full text |Cite
|
Sign up to set email alerts
|

Isocaloric Fructose Restriction Reduces Serum d-Lactate Concentration in Children With Obesity and Metabolic Syndrome

Abstract: Objective: To investigate the link between dietary sugar consumption and two separate pathogenetic mechanisms associated with metabolic syndrome: de novo lipogenesis (DNL) and non-enzymatic glycation. Design and participants: We assessed changes in serum D-lactate (the detoxification endproduct of methylglyoxal) concentration in response to nine days of isocaloric fructose restriction in 20 children with obesity and metabolic syndrome, and examined correlations with changes in DNL, liver fat, insulin sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
2
19
0
2
Order By: Relevance
“…The authors also elucidated the impact of the diet intervention on the methylglyoxal (MG) pathway [15,63,89,90,91], and surprisingly found that fructose restriction associated with marked reduction of D-lactate, a biomarker of MG metabolism. This change of D-lactate correlated with reduction of liver fat content and DNL [88]. These observations open a new perspective of the adverse metabolic effects of excess fructose intake.…”
Section: Metabolic Effects Of Fructose Consumptionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors also elucidated the impact of the diet intervention on the methylglyoxal (MG) pathway [15,63,89,90,91], and surprisingly found that fructose restriction associated with marked reduction of D-lactate, a biomarker of MG metabolism. This change of D-lactate correlated with reduction of liver fat content and DNL [88]. These observations open a new perspective of the adverse metabolic effects of excess fructose intake.…”
Section: Metabolic Effects Of Fructose Consumptionmentioning
confidence: 95%
“…The key metabolic and mechanistic issues of fructose consumption has been studied during a nine days isocaloric feeding study (fructose restriction to less than 4% of calories) in obese children ( n = 40) with MetS and a high habitual sugar consumption (>50 g/day) [61,87,88]. The metabolic assessment was extensive utilizing magnetic resonance imaging and stable isotope technology for DNL in addition to extensive biomarker platform.…”
Section: Metabolic Effects Of Fructose Consumptionmentioning
confidence: 99%
“…Other short-term investigations in obese children have shown that restricting fructose consumption reduces liver fat, DNL, and improves insulin sensitivity [88,89]. In contrast, studies involving fructose consumption in overweight/obese patients show that long-term or short-term consumption of excess fructose or glucose made no difference in parameters of metabolic-related conditions, such as inflammation, liver triglycerides levels, serum triglycerides, or insulin levels [90][91][92].…”
Section: Fructose Metabolism In Humans Is Variablementioning
confidence: 99%
“…It was found that hepatic fat accumulation was significantly improved by low sugar diet compared to normal diet [ 26 ]. Other studies have also shown a benefit from isocaloric restriction of fructose on various features including fatty liver, hypertriglyceridemia, and insulin resistance [ 25 , 27 , 28 ].…”
Section: Role Of Fructose Under Physiological and Pathological Conditmentioning
confidence: 99%